ACADEMIC ACHIEVEMENT OF HIGH SCHOOL STUDENTS IN RELATION TO THEIR EMOTIONAL STABILITY - Kalita, Sima (Journal of process management and new technologies, 2016)
In the present study an attempt was made to know the relationship between personality factor emotional stability and academic achievement of the high school students of South Kamrup district of Assam, India. Students were randomly selected from different high schools of the selected area. A sample of 400(both boys and girls) students was selected and Cattell’s Jr. High School Personality Questionnaire (HSPQ) was administered to them and record of academic achievement was collected from the school record. Subsequently the data were subjected to statistical analysis with the help of percentage analysis and x2 .Results indicated a significant relationship between emotional stability and academic achievement of high school students of South kamrup district, Assam, India. The study also depicted that high level of emotional stability leads to high academic achievement and low emotional stability leads to low level of academic achievement.